2010
DOI: 10.2166/wst.2010.914
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the employment of adsorption and coprecipitation agents for the removal of PPCPs in conventional activated sludge (CAS) systems

Abstract: Three activated sludge reactors were operated to improve the removal of organic micropollutants such as Pharmaceutical and Personal Care Products (PPCPs). Reactor 1 (R1) was operated as a Conventional Activated Sludge reactor (CAS), Reactor 2 (R2) consisted of a CAS unit that was continuously fed with FeCl3 whereas granular activated carbon (GAC) was fed directly into the mixed liquor of Reactor 3 (R3) in order to attain concentrations in the range 100-1,000 mg/L. PPCPs removal rates varied depending on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 18 publications
(23 reference statements)
3
10
2
Order By: Relevance
“…Table 3 shows the Langmuir and Freundlich isotherm parameters (q m and K f , respectively) for the compounds that demonstrated relatively rapid breakthrough from the GAC column. Our isotherm data conform to a general trend found in the literature regarding a relatively higher adsorption capacity of the neutral compounds carbamazepine (Nowotny et al, 2007;Serrano et al, 2010;Deegan et al, 2011) and metronidazole (Rivera-Utrilla et al, 2009) in comparison to that of the ionized compounds, namely, diclofenac (Nowotny et al, 2007;Serrano et al, 2010) and naproxen (Nowotny et al, 2007;Serrano et al, 2010). However, the isotherm parameters did not demonstrate any …”
Section: Adsorption Isothermssupporting
confidence: 90%
See 2 more Smart Citations
“…Table 3 shows the Langmuir and Freundlich isotherm parameters (q m and K f , respectively) for the compounds that demonstrated relatively rapid breakthrough from the GAC column. Our isotherm data conform to a general trend found in the literature regarding a relatively higher adsorption capacity of the neutral compounds carbamazepine (Nowotny et al, 2007;Serrano et al, 2010;Deegan et al, 2011) and metronidazole (Rivera-Utrilla et al, 2009) in comparison to that of the ionized compounds, namely, diclofenac (Nowotny et al, 2007;Serrano et al, 2010) and naproxen (Nowotny et al, 2007;Serrano et al, 2010). However, the isotherm parameters did not demonstrate any …”
Section: Adsorption Isothermssupporting
confidence: 90%
“…In the literature, several solute properties that influence the adsorption of organic contaminants onto activated carbon have been identified. These properties include, among others, solute hydrophobicity (De Ridder et al, 2010;Serrano et al, 2010), aromaticity (De Ridder et al, 2010), charge and size (De Ridder et al, 2010), and presence of specific functional groups (Westerhoff et al, 2005;De Ridder et al, 2010). The adsorption mechanisms related to these properties occur in parallel, and their respective dominance can vary from compound to compound (De Ridder et al, 2010;Dickenson and Drewes, 2010).…”
Section: Analysis Of Breakthrough Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kleywegt et al [244] investigated the removal of CBZ by GAC adsorption followed by UV photolysis that achieved effective removal of CBZ (93%). Serrano et al [203] investigated the removal of PhACs including CBZ in a CAS process followed by GAC adsorption. They reported that adsorption onto activated carbon improved the overall removal of CBZ by as much as 40% [203].…”
Section: Combined/hybrid Treatment Systemsmentioning
confidence: 99%
“…Serrano et al [203] investigated the removal of PhACs including CBZ in a CAS process followed by GAC adsorption. They reported that adsorption onto activated carbon improved the overall removal of CBZ by as much as 40% [203].…”
Section: Combined/hybrid Treatment Systemsmentioning
confidence: 99%